Triticale–annual ryegrass mixture effects on forage characteristics and performance of early-weaned beef calves - Vendramini, Joao M.B.; Arthington, John D.; Leite de Oliveira, Fabio C.; Aguiar, Andre D.; Moriel, Philipe; Sanchez, Joao M.D.; Filho, Cecilio V.S. [UNESP]; Yarborough, James K. (American Registry of Professional Animal Scientists, 2016)
Mixing small grains with annual ryegrass (Lolium multiflorum) may be a feasible management practice to improve forage production for early-weaned beef calves in the southeastern United States. The objective of this experiment was to evaluate forage characteristics and animal performance of early-weaned beef calves grazing annual ryegrass or annual ryegrass–triticale (X Triticosecale) mixed pastures. The experiment was conducted at Ona, Florida, from February to April 2011 (yr 1) and 2012 (yr 2). Treatments were annual ryegrass or triticale–annual ryegrass pastures distributed in a completely randomized design with 4 replicates. Four calves (mean initial BW = 100 ± 13 kg) were allocated to each pasture (0.3 ha) using a continuous and fixed stocking rate. Calves were supplemented daily with concentrate (16% CP and 78% TDN) at 1% BW. Herbage mass was greater (P = 0.01) for the triticale–annual ryegrass than annual ryegrass treatment in yr 1 (2,730 vs. 2,080 ± 100 kg/ha), but there was no difference (P = 0.87) between treatments in yr 2 (1,750 ± 120 kg/ha). The annual ryegrass treatment had greater CP (19.5 vs. 15.0 ± 0.7%) and in vitro OM disappearance (80.6 vs. 76.2 ± 1.7%) than the triticale–annual ryegrass in yr 2. Calf ADG decreased from February to April (P = 0.04) and was greater (P < 0.02) for annual ryegrass than triticale–annual ryegrass only in March (0.89 vs. 0.76 ± 0.05 kg/d). Lack of benefit to animal performance, cost of seed, and necessary adjustment in the supplement composition or quantity due to lesser nutritive value should be considered in the decision to use triticale–annual ryegrass mixed pastures for early-weaned calves.
Keywords: beef cattle; early-weaned calf; grazing management; triticale